Analysis of the Potential and Management Strategies of Mud Crab (Scylla spp.) Resources in the Bangka Belitung Islands Province, Indonesia - Devi Anggita; Anaya Noveleta; Dianatalia; Clara Dwi Ananta; Raihan Arrasyid; Sudirman Adibrata (Coastal and Marine Journal, 2025)
This study aims to analyze the potential of mud crab resources and formulate sustainable management strategies in the Bangka Belitung Islands Province. The research was conducted from April to May 2025 using a descriptive quantitative approach based on secondary data obtained from fisheries statistics, scientific publications, and relevant literature. Data analyzed included mud crab production, fishing gear utilization, and environmental conditions supporting mud crab habitats. The results showed that mud crab production in Bangka Belitung increased from 1,813.66 tons in 2020 to 3,854.27 tons in 2024, despite fluctuations in the number of trap nets (bubu) used by fishermen. Regression analysis indicated a moderate relationship between the number of trap nets and mud crab production, suggesting that production is influenced not only by fishing effort but also by environmental conditions, bait quality, and fishing techniques. Sustainable management strategies should focus on mangrove habitat conservation, regulation of minimum catch size, prohibition of harvesting berried female crabs, environmentally friendly fishing practices, development of mud crab aquaculture, and strengthening community participation. These strategies are expected to support the sustainability of mud crab resources and improve the welfare of coastal communities in IFMA 711.